Uji Cemaran Logam Mangan (Mn), Tembaga (Cu), dan Mikroba pada Air Minum dalam Kemasan : Testing for Manganese (Mn), Cooper (Cu), and Microbial Contamination in Bottled Drinking Water - Rosita, Tita; Sadiyah, Inne (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2024)
The presence of metal contaminants such as Manganese (Mn) and Copper (Cu) and microbial contaminants in bottled drinking water (AMDK) that are potentially harmful to human health must be maintained so as not to exceed the set limits. The standard method of testing for Mn and Cu metal contamination in bottled water involves the use of Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) which refers to SNI 3554:2015. Microbial contamination testing in bottled water was carried out by measuring several parameters such as total plate count (ALT), Coliform test, E.coli test and Pseudomonas aeruginosa test with methods referring to SNI 3554:2015. The test results show that the level of Mn metal in AMDK is 0.001 mg/L with a very low relative variation (%RSD 0.00%), and the level of Cu metal is 0.004 mg/L with the same low relative variation (%RSD 0.00%). In addition, the microbial contamination test results for total plate counts were <1 CFU/mL, and the average test results for E.coli, Coliform, and P.aeruginosa bacteria were 0 colonies/250 mL samples. These results illustrate that the levels of Mn and Cu metal contamination and microbial contamination found in AMDK do not exceed the limits set in SNI 3553: 2015. Based on the tests conducted, bottled drinking water is proven safe from Mn and Cu metal contamination and microbial contamination.